The Impact of E-cigarette Promotion by Influencers on Instagram, TikTok, and YouTube on Vaping Behavior Among Teenagers - Fitrina Windyastami Dewi; Tiara Amelia; Rohman Daka (JURNAL KESMAS DAN GIZI (JKG), 2026)
Social media platforms such as Instagram, TikTok, and YouTube have become the main platforms for the promotion of e-cigarettes by influencers, which influences vaping behavior among adolescents. Positive content, such as “vape tricks” and gender-based marketing, reinforces the perception that vaping is safe and attractive. Objective: This study aims to analyze the impact of e-cigarette promotion by influencers on social media on vaping behavior among adolescents (aged 13-23 years) through a systematic review of the literature. Methods: A systematic review was conducted using databases such as ScienceDirect, PubMed, and Google Scholar with keywords such as “e-cigarette promotion”. Inclusion criteria included English-language articles (2020-2025) discussing e-cigarette promotion by influencers on Instagram, TikTok, or YouTube. Literature selection used the PRISMA method, resulting in 10 articles from 835 initial articles after screening for duplication and eligibility criteria. Results: E-cigarette promotion was dominated by content with “vape tricks” and gender-based marketing strategies reinforcing the normalization of vaping. TikTok increased the risk of e-cigarette use, while YouTube promoted product reviews and discounts. The lack of health narratives exacerbated adolescents' knowledge gap about the risks of vaping. Conclusion: Influencer promotion of e-cigarettes on social media increases the normalization and behavior of vaping among adolescents, driven by visual content Strict regulations and social media-based educational campaigns are needed to protect adolescents from the influence of this promotion.